DOEGE-POTTER SYNDORME: A RARE CASE OF METASTATIC HEMANGIOPERICYTOMA WITH PERSISTENT HYPOGLYCEMIA IN A 27-YEAR-OLD MALE - VLD, Zarra; KJN, Demegillo; N, Naranjo (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Doege-Potter syndrome (DPS) is a rare paraneoplastic condition characterized by hypo insulinemic hypoglycemia secondary to a solitary fibrous tumor. The underlying mechanism is secretion of pro-insulin-like growth factor (IGF) II by the tumor which causes decreased release of glucose into the circulation resulting to hypoglycemia. Only forty-five (45) cases of DPS have been reported since 1979 worldwide. CASE This is a case of a 27-year-old Filipino male who had multiple admissions due to the recurrence of a right temporo-zygomatic mass. He underwent excision five times and eventually was subjected to radiotherapy. The patient was asymptomatic with no evidence of disease for two years until a recent consultation was sought due to hypoglycemia presenting as seizure and decrease in sensorium. Metastatic work-up revealed multiple metastases in the liver, the lungs and the right adrenal gland; hence, a suspicion of hypoglycemia as a paraneoplastic event was entertained. This was confirmed by a 72-hour fast protocol which ruled out Insulinoma and pointed towards a non-islet cell tumor as the culprit of hypoglycemia. The patient was initially managed with continuous dextrose infusion, increase in caloric intake and steroids which ameliorated hypoglycemic episodes. He was eventually started on a weekly doxorubicin as a palliative treatment with an intent of lessening the tumor burden. CONCLUSION Due to its complexity, the management of DPS from a metastatic hemangiopericytoma was challenging and required a multidisciplinary approach; hence, an early screening for metastases was emphasized to prevent the undesirable sequelae of this disease process.